Komunikasi Antarbudaya Dalam Interaksi Beragama Di Pura Bukit Karangasem - I Gusti Ayu Ratna Pramesti Dasih (Jurnal Penelitian Agama Hindu, 2021)
The process of social interaction in the community is very close to communication and culture because of the harmonious reciprocal relationship. Culture and communication influence each other. Cultural differences will have the potential to cause uncertainty and anxiety disorders, so that the possibility of cultural shock occurs. The existence of a shift in the value of diversity, an important role of intercultural communication in bridging the obstacles to understanding society can be explained by intercultural interactions so as not to cause misunderstandings. This article analyzes the role of intercultural communication in religious interactions at Pura Bukit Kampung Anyar Karangasem using qualitative research methods. The results showed that: first, the historical background of the conquest of the Karangasem Kingdom over Lombok. Second, the process of adaptation and intercultural interaction carried out by Hindus and Sasak Bayan ethnic people creates religious social beliefs. Third, intercultural communication has implications for socio-religious interactions, such as: implications for religious values, implications for socializing activities, implications for the value of solidarity, and implications for the value of tolerance.